DETERMINANTS OF STUNTING AMONG CHILDREN AGED 12–59 MONTHS - Dahliansyah Dahliansyah; Desi Desi; Ayu Rafiony; Nopriantini Nopriantini; Ismi Trihardiani (Poltekkes Kemenkes Pontianak, 2026)
Background : Stunting is a manifestation of chronic malnutrition in children under five and has long-term consequences for physical growth, cognitive development, economic productivity, and the risk of non-communicable diseases in adulthood. Although the prevalence of stunting in Indonesia has shown a declining trend, it remains above the national target of less than 14%. Landak Regency is one of the areas with a relatively high prevalence of stunting in West Kalimantan Province. This study aimed to analyze the determinants of stunting among children aged 12–59 months in Landak Regency. Methods : A cross-sectional study design was used, involving 214 children aged 12–59 months. Data were collected in 2024 and analyzed descriptively and bivariately to assess the associations between risk factors and stunting. The variables examined included birth history, breastfeeding practices, child health status, deworming medication, and utilization of health services. Results : The results showed that most children had received basic health services, including complete immunization (96.7%), vitamin A supplementation (88.3%), and exclusive breastfeeding (92.1%). Bivariate analysis showed that deworming (p = 0.02) and exclusive breastfeeding (p = 0.04) were significantly associated with stunting. Children who did not receive exclusive breastfeeding and deworming had a higher proportion of stunting than those who received these interventions. Birth weight, birth length, early initiation of breastfeeding, history of illness, and frequency of health-post visits were not significantly associated with stunting. Conclusions: The findings emphasize the importance of exclusive breastfeeding practices and disease-prevention interventions, particularly deworming, as part of efforts to reduce stunting in Landak Regency.